"I'd rather be dead than disabled"—the ableist conflation and the meanings of disability. Issue 3 (3rd July 2017) - Reynolds, Joel Michael
ABSTRACT: Despite being assailed for decades by disability activists and disability studies scholars spanning the humanities and social sciences, the medical model of disability—which conceptualizes disability as an individual tragedy or misfortune due to genetic or environmental insult—still today structures many cases of patient–practitioner communication. Synthesizing and recasting work done across critical disability studies and philosophy of disability, I argue that the reason the medical model of disability remains so gallingly entrenched is due to what I call the "ableist conflation" of disability with pain and suffering. In an effort to better equip healthcare practitioners and those invested in health communication to challenge disability stigma, discrimination, and oppression, I lay out the logic of the ableist conflation and interrogate examples of its use. I argue that insofar as the semiosis of pain and suffering is structured by the lived experience of unwelcome bodily transition or variation, experiences of pain inform the ableist conflation by preemptively tying such variability and its attendant disequilibrium to disability. I conclude by discussing how philosophy of disability and critical disability studies might better inform health communication concerning disability, offering a number of conceptual distinctions toward that end.